Sejarah Masuknya Islam di Masa Awal Nusantara - Awalia, Anggi Ria; Rama, Bahaking; Rusmin B, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Studying the history of Islam in Indonesia is an interesting topic of research and study. However, it is not easy to trace the history of the entry of Islam into the archipelago. There is a lot of literature discussing the history of Islam in Indonesia. However, some information about the history of Islam in Indonesia is still based on the literature of Western scholars. Of course, this information still raises questions and doubts among various parties, especially among Islamic historians. For this reason, this paper will discuss further the theory of the entry of Islam in Indonesia, the strategy of spreading Islam in Indonesia, and Islamic education in the early days in Aceh Darussalam. The results of this study indicate that the theory of the arrival of Islam in the archipelago is based on its place of origin, namely the Arabic theory, the Chinese theory, the Persian theory, the Indian theory and the Turkish theory. The spread of Islam in Indonesia was mostly carried out through trade, preaching, marriage, education, and the Islamization of culture. In Aceh, most of the ulama are graduates of Islamic boarding schools. Acehnese society is strongly influenced by religious institutions that function as social controllers. Religious institutions such as Islamic boarding schools are places of education to form noble morals. The values and attitudes of the Acehnese people reflect Islamic character in almost all aspects. Those who became militant clerics were born through dayah education, and they were able to lead the community towards religious deepening and the process of Islamization. At that time, the government institutions responsible for education and science in Aceh were Balai Seutia Hukama, Balai Seutia Ulama, and Balai Jamaah Himpunan Ulama.